Kenya: Cost effective options for inclusive and sustainable development - Aragie, Emerta A.; Pauw, Karl; Thurlow, James; Jones, Eleanor (International Food Policy Research Institute, 2025)
In this policy brief, we present findings of a systematic evaluation and ranking of investment options for Kenya’s agrifood system based on their cost-effectiveness in achieving multiple development outcomes, including agrifood gross domestic product (GDP) growth, agrifood job creation, poverty reduction, declining undernourishment, and lowering diet deprivation. Additionally, the study assesses their environmental footprint, focusing on water consumption, land use, and emissions. Investments in small and medium enterprise (SME) processors, irrigation, and seed subsidy are shown to be the most cost-effective at driving improvements in social outcomes, like poverty and undernourishment. They are also highly ranked in terms of expanding agrifood GDP and employment. Expansion in extension and advisory services for seeds and agronomy as well as improvements in seed systems also rank high. However, many cost-effective investments have relatively high environmental footprints, which highlights potential tradeoffs. The study further reveals shifts in the cost-effectiveness ranking of investment options overtime and when extreme production shocks occur.